A Javanese Dance is A Representation of Rasa in Javanese Culture - Indah Sulastuti, Katarina; Sunardi; Efrida; Mamik Widyastuti; Hadawiyah Endah Utami; Setya Widyawati; Budi Setyastuti; Nuryanto (Institut Seni Indonesia Denpasar, 2024)
This paper presents the concept of rasa in Javanese culture embodied in Javanese dance. The ethnographic approach in the Ethnochoreology discipline used as a step in data collection was in-depth interviews with actors (dancers, choreographers) in a society with a Javanese cultural scope. The observation step in the data collection effort was carried out using the involved observation model or participant observer, completed by data collection through literature and relevant documents. The theoretical perspective and concept used as the basis for thinking in discussing the case study of the Ela-ela dance in this paper is the concept of rasa, as put forward by Paul Stange. Namely, that rasa is a